MelLec Exacerbates the Pathogenesis of Aspergillus fumigatus-Induced Allergic Inflammation in Mice - Tone, Kazuya; Stappers, Mark H. T.; Hatinguais, Remi; Dambuza, Ivy M.; Salazar, Fabián; Wallace, Carol; Yuecel, Raif; Morvay, Petruta L.; Kuwano, Kazuyoshi; Willment, Janet A.; Brown, Gordon D. (Frontiers in Immunology, 2021)
Environmental factors, particularly fungi, influence the pathogenesis of allergic airway inflammation, but the mechanisms underlying these effects are still unclear. Melanin is one fungal component which is thought to modulate pulmonary inflammation. We recently identified a novel C-type lectin receptor, MelLec (Clec1a), which recognizes fungal 1,8-dihydroxynaphthalene (DHN)-melanin and is able to regulate inflammatory responses. Here we show that MelLec promotes pulmonary allergic inflammation and drives the development of Th17 T-cells in response to spores of Aspergillus fumigatus. Unexpectedly, we found that MelLec deficiency was protective, with MelLec-/- animals showing normal weight gain and significantly reduced pulmonary inflammation in our allergic model. The lungs of treated MelLec-/- mice displayed significantly reduced inflammatory foci and reduced bronchial wall thickening, which correlated with a reduced cellular influx (particularly neutrophils and inflammatory monocytes) and levels of inflammatory cytokines and chemokines. Notably, fungal burdens were increased in MelLec-/- animals, without apparent adverse effects, and there were no alterations in the survival of these mice. Characterization of the pulmonary T-cell populations, revealed a significant reduction in Th17 cells, and no alterations in Th2, Th1 or Treg cells. Thus, our data reveal that while MelLec is required to control pulmonary fungal burden, the inflammatory responses mediated by this receptor negatively impact the animal welfare in this allergic model.